Combination Therapy with Flucytosine Improves Survival in AIDS-Related Cryptococcal Meningitis - Lake, Noelle (MD Conference Express, 2011)
The first randomized, controlled trial to show a survival benefit of an antifungal treatment in HIV-infected patients with cryptococcal meningitis was completed this year in Vietnam [ISRCTN 95123928].